E-portfolios and English teacher education in Brazil - Xavier, Margaret Malia Spofford (Revista Leitura, 2019)
This article discusses the theory and implementation of a network of e-portfolios in the English as a Foreign Language (EFL) teaching practicum at a Brazilian public university. E-portfolios effectively motivate Brazilian student teachers to value the work produced during the teaching practicum, while contributing to the development of digital literacy and professional identity in a globalized world, in which English plays a key role. The use of the e-portfolio as a complement to traditional final reports constitutes a shift in episteme from isolated report to interconnected site, thus impacting student teachers’ image of themselves and of EFL teaching. DOI: 10.28998/2317-9945.2014v1n53p155-180